Periprosthetic fractures after shoulder arthroplasty: a systematic review - Maciej Otworowski; Dariusz Grzelecki; Krzysztof Starszak; Andrzej Boszczyk; Mateusz Piorunek; Bartłomiej Kordasiewicz (EFORT Open Reviews, 2023)
Purpose: The goal of this study was to review available literature on periprosthetic shoulder fractures to evaluate epidemiology, risk factors and support clinical decision-making regarding diagnostics, preoperative planning, and treatment options. Methods: Two authors cross-checked the PubMed and Web of Science medical databases. The inclusion criteria were as follows: original human studies published in English, with the timeframe not limited, and the following keywords were used: ‘periprosthetic shoulder fracture,’ ‘total shoulder arthroplasty periprosthetic fractures,’ ‘total shoulder arthroplasty fracture,’ and ‘total shoulder replacement periprosthetic fracture.’ Seventy articles were included in the review. All articles were retrieved using the aforementioned criteria. Results: The fracture rate associated with total shoulder arthroplasty varied between 0 and 47.6%. Risk factors for periprosthetic fractures were female gender, body mass index < 25 kg/m2, smoking, rheumatoid arthritis, and Parkinson’s disease. The most commonly used classification is the Wright and Coefield classification. Periprosthetic fractures can be treated both, conservatively and operatively. Conclusion: Periprosthetic fracture frequency after shoulder arthroplasty ranges from 0 to 47.6%. The most common location of the fracture is the humerus and most commonly occurs intraoperatively. The most important factor influencing treatment is stem stability. Fractures with stem instability require revision arthroplasty with stem replacement. Fractures with a stable stem depending on the location, displacement and bone stock quality can be treated both conservatively and operatively. For internal fixation plates with cables and screws are most commonly used.